2021
DOI: 10.1177/0145561320986030
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Maxillary Sinus Balloon Sinuplasty and ESS

Abstract: Objectives: The aim of this controlled follow-up study was to compare the need for revision surgery, long-term efficacy, and satisfaction in chronic rhinosinusitis patients who had undergone maxillary sinus operation with either balloon sinuplasty or traditional endoscopic sinus surgery (ESS) technique. Methods: Thirty-nine ESS patients and 36 balloon patients of our previously described cohort, who had been primarily operated in 2008 to 2010, were contacted by phone. Symptoms, satisfaction, and need for revis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Study and patient characteristics of the selected studies : Study characteristics are presented in Table 1. Of 18 studies included in qualitative review, 9 were RCTs 9,12,16-22 , 9 were cohort 10,13,15,23-28 studies. When multiple articles reported on the same patient cohort, all studies were included in narrative review but only the study with the most complete result reporting was included in quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Study and patient characteristics of the selected studies : Study characteristics are presented in Table 1. Of 18 studies included in qualitative review, 9 were RCTs 9,12,16-22 , 9 were cohort 10,13,15,23-28 studies. When multiple articles reported on the same patient cohort, all studies were included in narrative review but only the study with the most complete result reporting was included in quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…37 However, the indications for balloon sinuplasty are more limited than ESS, 38,39 and there is evidence that patients undergoing balloon sinuplasty require revision surgery more frequently than conventional ESS patients. 40 As such it will not fully replace conventional ESS, but may have a more significant role in practice in England if local anaesthetic procedure facilities are improved. Although it is difficult to predict how balloon sinuplasty will affect ESS day-case rates, the future use of balloon sinuplasty and its outcomes should be monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon sinuplasty is thought to have a complication risk similar to conventional ESS 37 . However, the indications for balloon sinuplasty are more limited than ESS, 38,39 and there is evidence that patients undergoing balloon sinuplasty require revision surgery more frequently than conventional ESS patients 40 . As such it will not fully replace conventional ESS, but may have a more significant role in practice in England if local anaesthetic procedure facilities are improved.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Endoscopic sinus surgery and septal modification are also effective treatments for chronic rhinosinusitis. 9 Major components of the nasal septum include cartilage, the vomer extending upward from the hard palate, and the perpendicular plate of the ethmoid bone extending downward from the anterior skull base. Septal deviation and individual anatomy can lead to difficulty visualizing operative trajectories in transsphenoidal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is likely not relevant to surgical access to the sella and skull base region. 9 Melroy et al reported a complication rate of 0.0035% per sinus when reviewing balloon septoplasty for nasal access in an FDA database. 11 Our patient had a successful tumor resection and did not note any postoperative complications.…”
Section: Discussionmentioning
confidence: 99%